2019
DOI: 10.3847/1538-4357/ab1756
|View full text |Cite
|
Sign up to set email alerts
|

The Inner Disk and Accretion Flow of the Close Binary DQ Tau

Abstract: We present multi-epoch optical and near-infrared (NIR) photometry and spectroscopy of the spectroscopic binary T Tauri star DQ Tau. The photometric monitoring, obtained using SMARTS ANDICAM, recovers the previously-seen correlation between optical flux and the 15.8-day binary orbital period, with blue flux peaks occurring close to most observed periastron passages. For the first time, we find an even more consistent correlation between orbital period and NIR brightness and color. The onset of pulse events in t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 55 publications
3
20
0
Order By: Relevance
“…Our results that the accretion depends on the orbital phase and is highest nearby periastron support previous observational and numerical results in the literature for DQ Tau and for eccentric binary systems in general (e.g. Mathieu et al 1997;Günther & Kley 2002a;Salter et al 2010;D'Orazio et al 2013;Farris et al 2014a;Muñoz & Lai 2016;Tofflemire et al 2017;Kóspál et al 2018;Muzerolle et al 2019). This is in agreement with the hypothesis that the accretion flow of DQ Tau can be explained by the "pulsed accretion model" (Artymowicz & Lubow 1996), according to which the accretion is highly modulated by the binaries orbital motion, peaking during periastron passages.…”
Section: Accretion Luminosity and Mass Accretion Ratesupporting
confidence: 91%
See 3 more Smart Citations
“…Our results that the accretion depends on the orbital phase and is highest nearby periastron support previous observational and numerical results in the literature for DQ Tau and for eccentric binary systems in general (e.g. Mathieu et al 1997;Günther & Kley 2002a;Salter et al 2010;D'Orazio et al 2013;Farris et al 2014a;Muñoz & Lai 2016;Tofflemire et al 2017;Kóspál et al 2018;Muzerolle et al 2019). This is in agreement with the hypothesis that the accretion flow of DQ Tau can be explained by the "pulsed accretion model" (Artymowicz & Lubow 1996), according to which the accretion is highly modulated by the binaries orbital motion, peaking during periastron passages.…”
Section: Accretion Luminosity and Mass Accretion Ratesupporting
confidence: 91%
“…This interpretation has been confirmed in the following DQ Tau accretion studies (e.g. Salter et al 2010;Tofflemire et al 2017;Kóspál et al 2018;Muzerolle et al 2019). However, while the on-average results confirm the model predictions, Tofflemire et al (2017) found a complex variability from epoch to epoch, suggesting that the material accretes from the inner edge of the CBD in a more complex way than predicted by models.…”
Section: Introductionsupporting
confidence: 58%
See 2 more Smart Citations
“…In the case of highly eccentric binaries, like TWA 3A (the subject of this study), accretion bursts are predicted near each periastron passage that increase the specific accretion rate by a factor of ∼10 (Muñoz & Lai 2016). Evidence for such orbit-modulated accretion has been shown in the highly eccentric binaries DQ Tau (e=0.57; Mathieu et al 1997;Tofflemire et al 2017a;Muzerolle et al 2019) and TWA 3A (e=0.63; Tofflemire et al 2017b) through long-term photometric monitoring. Additionally, DQ Tau has also shown periodic increases in the level of absorption line veiling and Hα luminosity near periastron ).…”
Section: Introductionmentioning
confidence: 67%